Practicing community development principles in our barangays - De Leon, Alwin B (Quezon City, 2005)
This book is the product of my involvement in community development work since 1991. More than a decade of exposure to both urban and rural settlers, including the Aeta tribal communities, has continuously taught me about the plight of impoverished communities and marginalized sectors in our society.
Keywords: Community development- Philippines; Non-Government organizations- Philippines